The Disabled and the Law Throughout the World - Thornburgh, Dick (Journal of religion in disability & rehabilitation, 1994)
This address was delivered to the Seventh International Conference of the Pontifical Council for Pastoral Assistance to Health Care Workers. It articulates the place and need for the field of law to participate in laying groundwork for persons with disabilities to achieve fuller involvement and fulfillment in all aspects of society.